2006
DOI: 10.1215/15228517-2005-012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of melanoma brain metastases using engineered neural stem/progenitor cells1

Abstract: Brain metastases are an increasingly frequent and serious clinical problem for cancer patients, especially those with advanced melanoma. Given the extensive tropism of neural stem/progenitor cells (NSPCs) for pathological areas in the central nervous system, we expanded investigations to determine whether NSPCs could also target multiple sites of brain metastases in a syngeneic experimental melanoma model. Using cytosine deaminase-expressing NSPCs (CD-NSPCs) and systemic 5-fluorocytosine (5-FC) pro-drug admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 27 publications
3
127
0
1
Order By: Relevance
“…This tropism has been exploited to deliver multiple therapeutic genes or cDNAs selectively to tumor foci (summarized in Table 1; stem and progenitor cells for tumor-selective therapy). 3,10,[15][16][17][23][24][25][26][27][28][29][30][31] The central question to be addressed then becomes whether we can exploit the inherent ability of these cells to migrate to, infiltrate and-when desirable-engraft to 'correct' pathologies in patients. The long-range goal is complete cure without toxic side effects or relapse.…”
Section: Introductionmentioning
confidence: 99%
“…This tropism has been exploited to deliver multiple therapeutic genes or cDNAs selectively to tumor foci (summarized in Table 1; stem and progenitor cells for tumor-selective therapy). 3,10,[15][16][17][23][24][25][26][27][28][29][30][31] The central question to be addressed then becomes whether we can exploit the inherent ability of these cells to migrate to, infiltrate and-when desirable-engraft to 'correct' pathologies in patients. The long-range goal is complete cure without toxic side effects or relapse.…”
Section: Introductionmentioning
confidence: 99%
“…In NSC-based gene therapy strategies targeting brain tumors, NSCs were mostly used to transport the CD/5-FC prodrug system to the tumor cells. [3][4][5][6][7][8] Recently, Dickson et al 21 showed that in mice, F3 human NSCs transiently expressing human IFN-b displayed tropism for sites of disseminated neuroblastoma, resulting in significant tumor growth. The sustained expression of IFN-b at disseminated sites of microscopic disease represents a novel therapeutic approach.…”
Section: F3cdifn-b Cells Increase the Survival Periods In Experimenmentioning
confidence: 99%
“…In particular, NSCs that are retrovirally transduced with suicide genes such as the cytosine deaminase (CD) gene show a remarkable 'bystander killer effect' on 5-fluorocytosine (5-FC)-treated glioma cells. 3,[5][6][7][8] Interferon-b (IFN-b) is known for its ability to interfere with viral replication and also for its antiproliferative effects on a variety of cancer cells. However, the efficacy of IFN-b is limited because of its extremely short half-life after intravenous administration as well as the systemic toxicity when this protein is administered at doses required to achieve the desired antitumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…As neural stem cells (NSCs) are able to target tumor cells, molecular therapies using these cells can be used to produce antitumor effects in tumor lesions. 8,9 As gene/prodrug systems can be designed to more selectively target tumor cells than normal cells, 10 the application of enzyme/ prodrug systems to minimize side effects has received much attention. The cytosine deaminase (CD)/5-fluorocytosine (5-FC) system, 11--13 one of the gene-directed enzyme/prodrug therapies (GEPT), metabolically converts non-toxic 5-FC into the toxic metabolite 5-FU 14 and inhibits DNA synthesis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%